2011
DOI: 10.1136/bmj.d5701
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative use of tranexamic acid to reduce transfusion rate in patients undergoing radical retropubic prostatectomy: double blind, randomised, placebo controlled trial

Abstract: Objectives To determine the efficacy of intraoperative treatment with low dose tranexamic acid in reducing the rate of perioperative transfusions in patients undergoing radical retropubic prostatectomy.Design Double blind, parallel group, randomised, placebo controlled trial.Setting One university hospital in Milan, Italy.Participants 200 patients older than 18 years and undergoing radical retropubic prostatectomy agreed to participate in the trial. Exclusion criteria were atrial fibrillation, coronary artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 29 publications
4
105
1
4
Order By: Relevance
“…Recent trials using tranexamic acid in ovarian cancer and prostate cancer surgery demonstrated decreased intraoperative blood loss and reduced transfusion rate [27,28]. This strategy is now being tested in RC patients in the Canadian multicenter Trial to Assess Chelation Therapy (TACT) [29].…”
Section: Discussionmentioning
confidence: 99%
“…Recent trials using tranexamic acid in ovarian cancer and prostate cancer surgery demonstrated decreased intraoperative blood loss and reduced transfusion rate [27,28]. This strategy is now being tested in RC patients in the Canadian multicenter Trial to Assess Chelation Therapy (TACT) [29].…”
Section: Discussionmentioning
confidence: 99%
“…Thaller and Beal also present detailed reports of six patients who have succumbed to haemorrhagic complications or had life-threatening exsanguinations secondary to isolated facial trauma [5]. TXA has also been reported to be successful in reducing haemorrhage in several surgical procedures including craniofacial surgery [6], knee surgery [7], spine surgery [8], prostrate surgeries [9] and the like besides trauma management. TXA oral rinse has been used for preventing excessive haemorrhage for patients with coagulopathies [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…These patients are treated with conservative proceedings such as antifibrinolytic agents. TXA, an antifibrinolytic drug, reported to be safe in most prior studies, had no serious side effects in our study [9,10]. The highest effectiveness of TXA is at first four hours after trauma and injection, so in our study, we started TXA administration immediately after diagnosis of EDH in patients [8].…”
Section: Discussionmentioning
confidence: 99%